A grounded theory of technical support in contact centers - Apag, Meldie A. (Animo Repository, 2018)
The contact center industry is a vast and rapidly expanding information technology-enabled services industry, where technical support representatives play an important role in customer facing operations, and therefore, it is relevant to understand the concerns of the representatives. Using the classic grounded theory method, it was discovered that the concern of technical support representatives in contact centers is providing quality service to angry customers, and to continually resolve this main concern, they follow a basic social process called techcalmsolving. The process involves using technology to calm angry customers and provide quality service in solving their problems. As a substantive grounded theory of inbound customer service, techcalmsolving, with its struggling, coping, and enjoying activities and strategies, has several theoretical and practical implications, including its applicability to distressed employees of organizations, and its potential utility for evaluating technical support effectiveness in contact centers.